Propuesta de un plan estratégico de marketing para la empresa comercializadora de electrodomésticos “Jhon Montero” en la ciudad Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2017 - Rodríguez Zambrano, Jenny Aracely (2017)
The present thesis research is focused and its main objective is to implement a strategic marketing plan that will improve the management and productivity of the company "JHON MONTERO", in the city of Nueva Loja, Province of Sucumbíos; In addition they have set specific objectives, the same ones that will serve for the achievement and fulfillment of the main objective. The methods used for the research were: the scientific, analytical, deductive, mathematical, historical, descriptive and statistical; the techniques used to obtain information were: observation, survey and interview; the instrument that was used for the collection of the information was the questionnaire. With the information obtained and analyzed in the different information tools, plus the surveys made to the population, employees and manager of the company, the internal and external aspects present in the company could be determined by way of diagnosis. It began by carrying out a study and analysis of the external situation to the company, in the general aspect (macro environment) and then in the specific aspect (micro environment), in the latter analyzing the forces of Porter and the information obtained in the surveys carried out To the canton market (382 surveys); In the same way the study and analysis of the internal aspect of the company was done, for which the information obtained in the interview was used to the manager of the company and, surveys carried out to the personnel who work in it. In the weighting of the results of external factors MEFE, resulting in a value of 2.71, a value that is above the average, and indicating at the same time that the position in front of the external situation is strong. On the other hand the analysis of the matrix of internal factors MEFI gives us as value 2, 70 indicating this, that the company presents a solid internal position. After the analysis of both the external and internal factors, an accurate reading of the current situation in which the company is found is made, so that the diagnosis is made using the SWOT matrix and determining the lines of action to be followed through The SWOT strategy matrix; Four major strategic objectives were identified and summarized in the matrix of the action plan, each objective with its respective budget. A total budget for the implementation of the strategic marketing plan in the company whose value is: $ 6,264.00. Therefore, it is concluded that the proposed strategic plan for the company "JHON MONTERO" will have a positive impact, take advantage of its adequate internal and external position, its implementation will be at a low cost, contribute to the economic development of the province, and will be of great Benefit for the growth and strengthening of this company.